PROGRAM PEMBERDAYAAN MASYARAKAT DALAM UPAYA PENINGKATAN KESEJAHTERAAN KELUARGA DI WILAYAH KELURAHAN SUNGAI ANDAI KOTA BANJARMASIN - Erma Ariyani; Avela Dewi; Hj Aulia (Jurnal PubBis, 2021)
ABSTRACT This research on community empowerment programs in Sungai Andai Kelurahan, Banjarmasin City aims to identify existing empowerment programs, then these programs will be evaluated to determine the form of programs that have a positive impact on improving family welfare. The method used in this study was the in-depth interview technique with the sub-district and community who were the target of the program. Then the data were analyzed using the Miles and Huberman technique. The results showed that there are several empowerment programs that have been implemented in Sungai Andai village, namely making salted eggs, making pastries, printing, sewing, embroidering, embroidering and food packaging processes. Some of these programs come from the Department of Industry and Trade of the city of Banjarmasin and also from village funds allocated specifically for empowerment programs. Based on information, these programs have not fully had a direct impact on improving the welfare of the community, because there are programs that have completed the implementation of training that cannot be followed up by the community independently due to constraints on financing. This research suggests that the kelurahan monitor and evaluate existing empowerment programs and provide assistance after training so that obstacles that arise in the next process can be resolved quickly. Keywords: Empowerment, Welfare, Community, Sungai Andai